2021
DOI: 10.1016/j.euo.2021.06.006
|View full text |Cite
|
Sign up to set email alerts
|

A European Model for an Organised Risk-stratified Early Detection Programme for Prostate Cancer

Abstract: Context: Overdiagnosis as the argument to stop pr.ostate cancer (PCa) screening is less valid since the introduction of new technologies such as risk calculators (RCs) and magnetic resonance imaging (MRI). These new technologies result in fewer unnecessary biopsy procedures and fewer cases of both overdiagnosis and underdetection. Therefore, we can now adequately respond to the growing and urgent need for a structured risk assessment to detect PCa early. Objective: To provide expert discussion on the existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 65 publications
0
56
0
1
Order By: Relevance
“…Hopefully, the progressive increase in studies involving the VOMs composition of PCa patients will help to unveil biomarkers suitable for its diagnosis, as a complementary tool to the current methods [ 15 ]. Recent studies have shown that the conjugation of PSA screening with other methodologies, such as risk calculators, biomarkers, and imaging tests, e.g., magnetic resonance imaging (MRI) or fusion biopsies, can attenuate overdiagnosis and under-detection issues [ 96 ]. This means that the combination of volatilomics with other methodologies could be extremely valuable for the classification and screening of cancer, being beneficial in the active surveillance of patients [ 7 ].…”
Section: Contribution Of the Omics Sciencementioning
confidence: 99%
“…Hopefully, the progressive increase in studies involving the VOMs composition of PCa patients will help to unveil biomarkers suitable for its diagnosis, as a complementary tool to the current methods [ 15 ]. Recent studies have shown that the conjugation of PSA screening with other methodologies, such as risk calculators, biomarkers, and imaging tests, e.g., magnetic resonance imaging (MRI) or fusion biopsies, can attenuate overdiagnosis and under-detection issues [ 96 ]. This means that the combination of volatilomics with other methodologies could be extremely valuable for the classification and screening of cancer, being beneficial in the active surveillance of patients [ 7 ].…”
Section: Contribution Of the Omics Sciencementioning
confidence: 99%
“…The classic approach of PCa detection based on systematic biopsies after PCa suspicion, has been disapproved due to the high rates of unnecessary biopsies and the over detection of insignificant tumours (iPCa) [2][3][4][5]. While PCa suspicion continues to be based on serum prostate-specific antigen (PSA) elevation or abnormal digital rectal examination (DRE), the detection of csPCa has improved since the introduction of multiparametric magnetic resonance imaging (mpMRI) and guided biopsies [6,7]. Nevertheless, there remain uncertain scenarios in which a high rate of unnecessary biopsies and over detection of iPCa occur [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…PI-RADS 3 remains the most uncertain scenario, in which csPCa usually does not reach 20% and in which more than 50% of the biopsied lesions reflect iPCa [9,15]. Prostate-specific antigen density (PSAD), MRI-based predictive models (MRI-PM), and modern markers are currently recommended for improving the selection of candidates for prostate biopsy [6,7,16].…”
Section: Introductionmentioning
confidence: 99%
“…This new diagnostic approach takes advantage of the high negative predictive value of mpMRI [ 4 ] and the increased csPCa sensitivity of guided biopsies [ 5 ]. The current decision-making with prostate biopsies is based on the Prostate Imaging-Report and Data System (PI-RADS) [ 6 ], and clinicians usually avoid prostate biopsies when the PI-RADS score is <3 due to the high negative predictive value of mpMRI for csPCa, reaching up to 95% [ 4 ]. In contrast, prostate biopsies are always recommended in men with PI-RADS > 3, due to the risk of csPCa higher than 50% in men with PI-RADS 4 and around 90% in those with PI-RADS 5 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%